HUBUNGAN DAYA TARIK JINGLE IKLAN DAN DAYA TARIK CELEBRITY ENDORSER SAL PRIADI DENGAN BRAND IMAGE IM3 OOREDOO (STUDI EKSPERIMEN PADA IKLAN “BULAN YANG BAIK”) - Nanda Immanuella; Agus Naryoso; Amida Yusriana (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2023)
Advertising is an important element of a series of product promotions that has an impact on how the brand image is perceived in the consumer's brain. IM3 Ooredoo uses advertising jingle and celebrity endorser Sal Priadi entitled